"It is hard to say 'no' to someone who wants to help": An exemplary model of corporate volunteer management and its challenges. Issue 4 (30th December 2021) - Liang, Xiaoyan; Amarakoon, Upamali; Bird, Susan; Pearson, David
Abstract: Despite the growth and popularity of corporate volunteering, a small, albeit growing stream of studies representing the nonprofit's perspectives focus on either "why" or "triple win" outcome of the corporate volunteer programs, not much is known about the process of internal management and strategy development of corporate volunteering programs. This study aims to examine the understudied strategy and management process of nonprofits in corporate volunteer‐related partnerships. Based on interview and observation data collected from 2018 to 2019 from an Australian nonprofit organization specializing in food rescue, the authors investigate its exemplary corporate volunteering management practices and the challenges it faces. Findings reveal three dimensions of management imperatives and two sets of management challenges that have not been addressed in the literature. This study advances corporate volunteer management literature from the nonprofit's perspective by providing a promising model for designing and implementing an effective corporate volunteer management program. It also highlights the ensuing challenges this model might face.